2003
DOI: 10.1063/1.1575734
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and dynamics of methylamine. I. Rotational and vibrational structures of CH3NH2 and CH3ND2 in à states

Abstract: Accurate and precise ionization energies of methylamines (CH 3 NH 2 and CH 3 ND 2 ) are determined to be 9.0422Ϯ0.0012 and 9.0532Ϯ0.0012 eV, respectively, by ͑1ϩ1Ј͒ two-photon mass-analyzed threshold ionization ͑MATI͒ spectroscopy. From selective ionizations from specified intermediate quantum states, fundamental frequencies of amino-wagging and CH 3 -rocking modes of CH 3 NH 2 ϩ (CH 3 ND 2 ϩ ) in D 0 states are determined to be 738 ͑573͒ and 1013 ͑1024͒ cm Ϫ1 , respectively. The frequency of the amino wag is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 41 publications
4
46
0
Order By: Relevance
“…[32][33][34] The most detailed spectroscopic analysis comes from Kim and co-workers, who have recorded 1+1 REMPI spectra of methylamine (as well as partially and fully deuterated isotopologues) and modeled the vibronic features using a hindered internal rotor Hamiltonian. [35][36][37] Spectra of the protiated methylamine show homogeneous broadening consistent with a lifetime of 0.38 ps at the origin and decreasing as the excitation energy increases. Analogous spectra of the partially deuterated methylamine-d2 species display sharper lines, and a longer excited state lifetime of around 8.8 ps.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…[32][33][34] The most detailed spectroscopic analysis comes from Kim and co-workers, who have recorded 1+1 REMPI spectra of methylamine (as well as partially and fully deuterated isotopologues) and modeled the vibronic features using a hindered internal rotor Hamiltonian. [35][36][37] Spectra of the protiated methylamine show homogeneous broadening consistent with a lifetime of 0.38 ps at the origin and decreasing as the excitation energy increases. Analogous spectra of the partially deuterated methylamine-d2 species display sharper lines, and a longer excited state lifetime of around 8.8 ps.…”
Section: Introductionmentioning
confidence: 76%
“…The effect of vibrational excitation in ν9 on passage through the conical intersection region was also noted by Waschewsky et al, who suggested that the anticipated vibrational excitation would lead to trajectories sampling regions of phase space in which the upper and lower adiabats are well separated. However, based on the more recent spectroscopic assignments of Kim and co-workers, [35][36][37] excitation at 222 nm likely prepares the 2ν7+2ν9 mode in S1, which as an even mode might be expected to favor formation of ground state products. In any event, this point is moot as it seems unlikely that the predicted barrier to direct dissociation on S1 can be overcome at any of the excitation wavelengths used.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][24][25] It displays intriguing dynamical features such as a huge H/D isotope effect, indicating that the N-H(D) bond dissociation occurs via tunnelling at the zero-point level of S 1 . [16][17][18][19][20][21] Predissociation dynamics is state dependent and the conical intersection seems to play an important role in the final product properties. 22 Even though product analyses reflect the exit dynamics, it is extremely hard to follow the trajectory back from the product to reactant for the irreversible chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its importance, methylamine and its deuterated isotopologues have been a target for numerous experimental and theoretical studies exploring their dissociation, [9][10][11][12][13][14][15][16][17] and structural and spectroscopic [18][19][20][21][22][23][24][25][26] properties. Most of the previous dissociation studies have been performed without characterizing the initial quantum state of the methylamine on the ground, X , or the first electronic state, Ã .…”
Section: Introductionmentioning
confidence: 99%